Fine mapping and transcriptomics reveal OSG function in regulation of grain size and pollen fertility in rice (Oryza sativa) - Sijie Zhao; Siyue Zhang; Weichen Xu; Sijia Fang; Mei Liu; Lei Wang; Xianyang Zhang; Bingxu Chen; Shuya Wei; Heming Zhao (PLoS ONE, 2026)
Grain shape is a critical factor that directly influences rice yield and quality, however, the molecular mechanisms underlying the regulation of grain shape development remains elusive. In this study, we characterized an oval-shaped grain mutant, osg , from the rice radiation mutagenesis mutant library via 60 Co-γ ray irradiation. Compared to ZH11, the osg mutant exhibited decreased grain length and thousand-grain weight but increased grain width and thickness, while displaying significantly reduced plant height, tiller number, pollen viability, and seed setting rate. Map-based cloning revealed that OsSRS3 , a known regulator of rice grain size and fertility, was identified as the candidate gene for OSG . The loss-of-function mutant in OsSRS3 exhibit abnormal phenotypes similar to that in osg . Comparative transcriptome sequencing of young panicles from ZH11 and osg showed that up-regulated genes were predominantly enriched in pathways related to plant hormone signal transduction and MAPK signaling, whereas down-regulated genes were mostly associated with starch and sucrose metabolism. Further analysis of differentially expressed genes (DEGs) within the pathways revealed that multiple DEGs in osg , such as OsJAZ11 , OsUgp1 and OsUgp2 , have been functionally characterized, and their mutant phenotypes align with those observed in osg . These findings provide a crucial foundation for elucidating the molecular mechanisms by which the SRS3 gene regulates grain size and fertility in rice.